Respuesta :
Answer:
B
Step-by-step explanation:
2x - 3 - x = 2 + 2x - 5
add like terms
x - 3 = -3 + 2x
subtract 2x to x on the other side
x - 3 = -3 + 2x
-2x - 2x
-x - 3 = -3
add 3 to the other side
-x - 3 = -3
+ 3 + 3
-x = 0
x = 0
Answer:
B) 2x-3-x=2+2x-5 has exactly one solution.
Step-by-step explanation:
A) -2x-1+5x=4+3x-1
-2x+5x-1=3x+3
3x-1=3x+3
3x-3x-1=3
0-1=3
-1=3
no solution
-----------------------
B) 2x-3-x=2+2x-5
x-3=2x-3
x-2x-3=-3
-x-3=-3
-x=-3+3
-x=0
x=0
Has exactly one solution.
-----------------------------------
C) 6x+2-4x=4+2x-8
2x+2=2x-4
2x-2x+2=-4
2=-4
no solution.
----------------------------
D) 5x+4x=3(3x-8)
9x=3(3x-8)
3x=3x-8
3x-3x=8
0=8
no solution.